âA POTENTIAL NONINVASIVE BIOMARKER OF NONALCOHOLIC STEATOHEPATITISâ - Oliveira, Yanaihara Pinchemel; Cotrim, Helma; Daltro, Carla; Alves, Erivaldo; Barros, Raffaelle (Journal of Medical Biomedical and Applied Sciences, 2018)
Background/Aim: Liver biopsy remains the gold standard for characterizing the histology of nonalcoholic fatty liver disease, yet this procedure is invasive. Oxidative stress plays an important role in the pathogenesis of steatohepatitis and erythrocytesare known to exert pro-oxidant activity. We hypothesized that erythrocytes damaged by oxidative stress could represent potential biomarkers capable of distinguishing steatosis from steatohepatitis. Methods: Our sample included 37 obese patients who underwent bariatric surgery and liver biopsy. Patients were classified according to histological diagnosis with respect to steatosis or steatohepatitis. Oxidative stress measurements were performed by chemiluminescence. Erythrocytes obtained from the whole blood of patients were stained to evaluate cell morphology by optical microscopy. Results: Higher levels of oxidative stress were seen in obese patients with steatohepatitis in comparison to those with steatosis (Cohens d=4.1). Erythrocytes damaged by oxidative stress were found in 81.2% of patients with steatosis and in 95.2% of the steatohepatitis cases (Phi= 0.22). These results were confirmed in an in vitro model. Oxidative stress levels were found to be elevatedin 60.6% of the cases in which modified erythrocytes were also present. Conclusions: The results indicated that altered erythrocytes may represent a novel noninvasive biomarker capable of distinguishing steatosis from steatohepatitis.